Etude comparative des caractéristiques écophysiologiques et des performances de croissance de l'huître creuse Crassostrea gigas diploïde et triploïde en milieu contrôlé - Haure, Joel; Fortin, Adeline; Dupuy, Beatrice; Nourry, Max; Palvadeau, Hubert; Papin, Mathias; Penisson, Christian; Martin, Jean-louis (2003)
Introduction: Marine farming in France is currently very widely dominated by oyster farming. French oyster production totals 148,467 tons, for a turnover of close to 280 million euros, making France the leading European producer. The two main species concerned are the cup oyster, Crassostrea gigas (140,000 tons) and the flat oyster, Ostrea edulis (2,000 tons), the production of which has collapsed since 1970 following successive epizootics of Marteilia refringens and Bonamia ostreae. French oyster farming is thus in a situation of quasi single-crop farming, with more than 90% of tonnage pertaining to the cup oyster (FAO data from 1993). This situation of quasi single-crop farming leads to the pessimistic observation that one hypothetical crisis in the French stocks, comparable to the one in 1970, would, a priori, leave no replacement alternative. Currently, there would be no substitute species with the characteristics of acclimatisation and resistance comparable to those of C. gigas in the event of high mortality (Boudry, pers. comm.). However, the diversification of species bred in oyster farming is indispensable in order to diversify the market and minimise the pathological risks that may put this occupational activity in danger. Thus, research has been done on the reintroduction of known species such as Crassostrea angulata (Huvet, 2000; Haure, 2001) or the optimisation of existing production of the flat oyster, O. edulis (Haure, 1999). This recent research, although promising, is not currently transferable to this occupation. In order to make the occupation of oyster farming durable, other avenues of research are being explored to improve the growth performance, survival and quality of the cup oyster, C. gigas. Recent studies based on the selection of genitors showed that there existed a genetic basis for the growth and survival of C. gigas (Ernande et al., 2000) but the inheritability of these characteristics must still be validated before adopting selection outlines. Other studies also aiming to optimise ...